2015
DOI: 10.7314/apjcp.2015.16.16.7167
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Rate Brachytherapy in Two 9 Gy Fractions in the Treatment of Locally Advanced Cervical Cancer - a South Indian Institutional Experience

Abstract: Background: Although 3D image based brachytherapy is currently the standard of treatment in cervical cancer, most of the centres in developing countries still practice orthogonal intracavitary brachytherapy due to financial constraints. The quest for optimum dose and fractionation schedule in high dose rate (HDR) intracavitary brachytherapy (ICBT) is still ongoing. While the American Brachytherapy Society recommends four to eight fractions of each less than 7.5 Gy, there are some studies demonstrating similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Various Studies have been done comparing toxicities with higher dose per fraction of BT. patients treated with ICR with a higher dose per fraction [22]. Majority of the toxicities occurred during the course of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Various Studies have been done comparing toxicities with higher dose per fraction of BT. patients treated with ICR with a higher dose per fraction [22]. Majority of the toxicities occurred during the course of radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Longer overall treatment time (> 56–60 days) have been linked to a greater probability of recurrence [ 16 , 21 ]. The overall treatment duration was 68 days in Arm A and 59 days in Arm B in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the limited infrastructure, shortage of trained staff and patient convenience, there has always been a compelling need to implement clinically feasible shorter fractionation schedules for HDR brachytherapy. As the shortest fractionation schedule, the 9 Gy × 2 regimen has, therefore, gained particular popularity in these regions, and numerous studies have demonstrated the safety and efficacy of this regimen [9][10][11]. In this context, it is noteworthy that many brachytherapy facilities in LMICs lack facilities for interstitial needle placement, solely depending on the use of intracavitary applications.…”
Section: Clinical Use Of the 9 Gy × 2 Regimenmentioning
confidence: 99%
“…Owing to the greater possibility of normal tissue sparing with advancements in technology, it has been possible to use larger fraction sizes, which allows earlier treatment completion [ 9 ]. In low resource regions, where patient turnover rates and treatment compliance are major issues, hypofractionation is widely employed for increasing patient turnover and treatment compliance with encouraging results [ 10 , 11 ].…”
Section: Issues With Brachytherapymentioning
confidence: 99%